The Observation of Performance Trends by Numerical Simulation with Different Parameters in a Nonlinear Reversible Solid Oxide Cell System - Jai-Houng Leu; Ay Su; Shun-Chi Kuo; Kuang-Chung Chen (Energies)
The reversible solid oxide cell model is established by COMSOL Multiphysics® (version 5.4) software under multi-physics coupling. According to the governing equation, the simulations were conducted based on the same parameters for many control groups numerically. At the same time, a comparison of these results was involved. For the air electrode in SOFC mode, the performance of the fuel cell will increase with the increase in the porosity. For the fuel electrode in SOFC mode, the increase is much greater than the impact of the porosity. The design parameters compared in this simulation are used to simulate and analyze and predict fuel cell performance under different conditions. The design parameters related to the electrode microstructure are defined in this model as: porosity (electrode porosity), pore size (electrode internal average pore size), and permeability (electrode internal permeability).